Absence of the right common carotid artery: Doppler ultrasonographic and MR angiographic findings. (October 2014) - Ulger, Fatma Esra Bahadır; Ulger, Aykut; Colak, Mustafa
We present a case of common carotid artery agenesis which is an extremely rare congenital anomaly. Less than 35 cases have been reported. These anomalies are typically asymptomatic and usually discovered as an incidental finding. Color Doppler ultrasonography is an effective and sensitive method for detecting absence of common carotid artery. But it is insufficient to identify the anomaly as a whole. Magnetic resonance angiography is a complementary technique to describe the origin of the external carotid artery and internal carotid artery.